PENGARUH KUALITAS ASET, LIKUIDITAS, DAN PROFITABILITAS TERHADAP TINGKAT KECUKUPAN MODAL PERBANKAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia) - Suharno, Rizki Ria Wulan Sari, Bambang Widarno & (Universitas Slamet Riyadi, 2016)
The purpose of this study was to analyze: 1) the impact asset quality on the bank's capital adequacy. 2) the effect of liquidity on the bank’s capital adequacy. 3) the effect of profitability on the bank’s capital adequacy and 4) the effect of asset quality, liquidity and profitability simultaneously on bank’s capital adequacy. This research is an empirical study on the bank listed on the Indonesia Stock Exchange. The type of data using quantitative and qualitative data. The study population was a conventional bank listed on the Indonesia Stock Exchange. Sampling techniques used sensus with a sample of 30 conventional banks. Source data used secondary data from website www.idx.co.id. Methods of data collection used documentation and literature study data were analyzed used classical assumption test and multiple linear regression analysis. The results showed that the quality of the assets has significant negative effect on the bank’s capital adequacy. Liquidity has positive but not significant effect on bank’s capital adequacy. Profitability has positive and significant effect on the bank’s capital adequacy. Asset quality, liquidity and profitability simultaneously significant effect on the bank’s capital adequacy.Keywords: asset quality, liquidity, profitability and capital adquacy